2001
DOI: 10.1016/s0014-5793(01)02967-2
|View full text |Cite
|
Sign up to set email alerts
|

TNFα‐induced glutathione depletion lies downstream of cPLA2 in L929 cells

Abstract: Both glutathione (GSH) depletion and arachidonic acid (AA) generation have been shown to regulate sphingomyelin (SM) hydrolysis and are known components in tumor necrosis factor K K (TNFK K)-induced cell death. In addition, both have hypothesized direct roles in activation of N-sphingomyelinase (SMase); however, it is not known whether these are independent pathways of N-SMase regulation or linked components of a single ordered pathway. This study was aimed at differentiating these possibilities using L929 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Arachidonic acid generated by PLA2 action has been shown to be a mediator of sphingomyelin hydrolysis induced by TNF-α in human leukemia-derived HL-60 cells [33,34]. It has also been demonstrated that, in L929 cells stimulated with TNF-α, arachidonic acid generated by the action of cytosolic PLA 2 causes glutathione depletion followed by sphingomyelinase activation [18]. Although in boar spermatozoa, no decrease in the levels of sphingomyelin during capacitating processes was found [35], further studies will be r e q u i r e d t o e x a m i n e t h e h y d r o l y s i s o f sphingomyelin after stimulation for acrosomal exocytosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arachidonic acid generated by PLA2 action has been shown to be a mediator of sphingomyelin hydrolysis induced by TNF-α in human leukemia-derived HL-60 cells [33,34]. It has also been demonstrated that, in L929 cells stimulated with TNF-α, arachidonic acid generated by the action of cytosolic PLA 2 causes glutathione depletion followed by sphingomyelinase activation [18]. Although in boar spermatozoa, no decrease in the levels of sphingomyelin during capacitating processes was found [35], further studies will be r e q u i r e d t o e x a m i n e t h e h y d r o l y s i s o f sphingomyelin after stimulation for acrosomal exocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…The sphingomyelin cycle has been recognized as an important signalling pathway involved in many cell types and, upon activation, s p h i n g o m y e l i n i s h y d r o l y z e d i n t o phosphorylcholine and ceramide, the latter playing an activator role [15,16]. A messenger role for ceramide in cells activated by tumour necrosis factor (TNF)-α [17,18], transforming growth factor-β [19], and 1α,25-dihydroxyvitamin D 3 [19] has been demonstrated. In human spermatozoa, the involvement of a sphingomyelin/ceramide pathway has been suggested as playing a role in the capacitating processes [21], and a neutral sphingomyelinase has been identified in ram spermatozoa [22].…”
mentioning
confidence: 99%
“…Several studies suggest that sphingomyelinases and ceramidases are activated in response to the same inducers that stimulate SK (11,(25)(26)(27)(28)(29), thus raising the possibility that sphingosine could be generated in or close to the plasma membrane concomitant with SK activation. These studies are consistent with S1P being generated in a location conducive for swift secretion out of the cell.…”
Section: Table I Effects Of Pkc Modulators On Sk Translocation In Hekmentioning
confidence: 99%
“…18) They were incubated with different concentrations of FA, FA-1, and FA-2 for 96 h. The supernatants were used for the TNF-a assay. A 100 ml of supernatant was added to 96-well microplates on which L929 cells were incubated; after 24 h, the number of cells were measured by MTT method.…”
mentioning
confidence: 99%